Highly formable aluminum alloys and methods of making aluminum alloy products thereof

JP2025032283APending Publication Date: 2025-03-11NOVELIS INC(US)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024216449
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-02-26
Filing Date
2024-12-11
Publication Date
2025-03-11

Smart Images

  • Figure 2025032283000001_ABST
    Figure 2025032283000001_ABST
Patent Text Reader

Abstract

To provide highly formable aluminum alloys and methods of making aluminum alloy products containing such alloys.SOLUTION: The method of preparing aluminum alloys described herein can include a low final cold reduction step and / or an optional inter-annealing step to produce randomly distributed crystallographic texture components that produce an isotropic aluminum alloy product improved in formability and deep drawability. The methods described herein result in aluminum alloy microstructures having a balance of alpha fibers and beta fibers that promote improved formability of aluminum alloy sheets. The resulting improvements in quality allow shaping processes with reduced rates of spoilage.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Patent Application No. 62 / 701,977, filed July 23, 2018, and U.S. Provisional Patent Application No. 62 / 810,585, filed February 26, 2019, each of which is incorporated herein by reference in its entirety.

[0002] The present disclosure relates to aluminum alloy products having a microstructure that facilitates shaping and forming of the aluminum alloy products. The present disclosure also relates to methods of making the aluminum alloy products. [Background technology]

[0003] Aluminum alloy sheets are increasingly replacing steel sheets for automotive parts, reducing the weight of automobiles while providing comparable mechanical properties, such as strength. However, improving the strength of aluminum alloy sheets often compromises the formability of these aluminum alloy sheets. For example, the formability of high-strength aluminum alloy sheets may be poor because the plastic anisotropy of the aluminum alloy sheets is not controlled by the forming process. The forming process creates a crystallographic texture of the aluminum alloy that promotes plastic anisotropy and plays an important role in the formability of the aluminum alloy.

[0004] Conventional processes for manufacturing aluminum alloy sheets include cold rolling steps to obtain a product having a fully recrystallized grain structure. In most cases, the aluminum alloy sheet is subjected to a high cold reduction in a final cold rolling step to produce the recrystallized grain structure. For example, the high cold reduction can be cold working to reduce the thickness of the aluminum alloy sheet by more than 70% in the final cold rolling step (e.g., the cold rolling step that results in the final gauge aluminum alloy product). However, the large amount of cold reduction in the final cold rolling stage results in an aluminum alloy microstructure with highly linear alpha fibers, e.g., aligned cube texture components. Aluminum alloy sheets with highly linear alpha fibers result in aluminum alloy sheets with anisotropic properties, e.g., low Lankford modulus (r-value), which leads to roping, edge cracking, etc. In this regard, it is desirable to optimize and / or control the manufacturing process of aluminum alloy products (e.g., aluminum alloy sheets) with isotropic properties. Summary of the Invention

[0005] The embodiments addressed herein are defined by the claims, not by this Summary. This Summary is a high-level overview of various aspects of the invention and introduces some concepts that are further described in the Detailed Description section below. This Summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used alone to determine the scope of the claimed subject matter. The subject matter should be understood by reference to appropriate portions of the entire specification, any or all drawings, and the claims.

[0006] Described herein are highly formable aluminum alloys and methods for making the aluminum alloys. In one aspect, a method of making an aluminum alloy product is described. The method includes casting an aluminum alloy to produce a cast aluminum alloy product, homogenizing the cast aluminum alloy product to produce a homogenized cast aluminum alloy product, hot rolling the homogenized cast aluminum alloy product to produce a hot rolled product, cold rolling the hot rolled product in a first cold rolling stage having a thickness reduction of about 25% to about 70% to produce a first cold rolled product having an intermediate gauge, and reducing the thickness of the first cold rolled product to the intermediate gauge. The gauge is then reduced by about 40% to about 70% in a second cold rolling step to the final gauge. In some cases, the method may further include producing a minium alloy product. The method may further include intermediate annealing the first cold rolled product. The intermediate annealing may be performed at an intermediate annealing temperature of about 300° C. to about 450° C. The gauge has a thickness of about 2 mm to about 6 mm. and optionally, solution treating the final gauge aluminum alloy product. The final gauge aluminum alloy product has a thickness of about 0.1 mm to about 3 mm. Optionally, the casting step includes direct chill casting or continuous casting. The homogenization step is carried out at a homogenization temperature of about 450° C. to about 600° C. The hot rolling step is carried out at a hot rolling temperature of about 500°C to about 560°C.

[0007] In some cases, the volume fraction of alpha fibers in the final gauge aluminum alloy product is In some cases, the final gauge aluminum alloy product The volume fraction of the beta fibers comprises at least about 6%. The ratio of the volume fraction of alpha fibers to the volume fraction of beta fibers in aluminum alloy products is approximately 0.5:1. 2:1. In some cases, the final gauge aluminum alloy product is isotropic. In some cases, the final gauge aluminum alloy product is made from intermediate gauge aluminum alloy. Final cold rolling with a reduction in thickness of more than 70% from the alloy to the final gauge aluminum alloy At least about 5% greater than the yield strength of an aluminum alloy produced by a method including the steps of: In some cases, the final gauge aluminum alloy product is subjected to intermediate 70% reduction in thickness from gauge aluminum alloy to final gauge aluminum alloy Ultimate tensile strength of aluminum alloys produced by a process including a final cold rolling step exceeding The ultimate tensile strength is at least about 3% greater than the ultimate strength. Final gauge aluminum alloy products are made by cutting intermediate gauge aluminum alloys into final gauge aluminium alloys. by a process including a final cold rolling step with a reduction in thickness of more than 70% to the aluminum alloy It has a total elongation that is at least about 5% greater than the total elongation of the aluminum alloy from which it is made.

[0008] Optionally, the aluminum alloy contains about 0.5-2.0 wt. % Si, 0.1-0. .4 wt% Fe, max 0.4 wt% Cu, max 0.5 wt% Mg, 0.02-0. 1 wt% Mn, max 0.02 wt% Cr, max 0.15 wt% Ti, max 0.1 wt% % by weight of Zn, up to 0.15% by weight of impurities, and Al. The aluminum alloy contains about 0.7-1.4 wt% Si, 0.1-0.3 wt% Fe, and a maximum of 0. 2 wt% Cu, max. 0.4 wt% Mg, 0.02-0.08 wt% Mn, max. 015% by weight Cr, max 0.05% by weight Ti, max 0.1% by weight Zn, max 0.1 5% by weight of impurities, and Al. In some cases, the aluminum alloy has a content of about 1.0 ~1.4 wt% Si, 0.12-0.20 wt% Fe, max 0.15 wt% Cu, Maximum 0.35 wt.% Mg, 0.04-0.08 wt.% Mn, 0.01-0.02 wt.% % Cr, max 0.02 wt.% Ti, max 0.04 wt.% Zn, max 0.15 wt.% and Al. In some cases, the final gauge aluminum alloy product contains It is an automobile body part.

[0009] Described herein is a ferromagnetic alloy containing about 0.5-2.0 wt. % Si, 0.1-0.4 wt. % F. e, Cu up to 0.4 wt%, Mg up to 0.5 wt%, Mn 0.02-0.1 wt% , max. 0.02 wt.% Cr, max. 0.15 wt.% Ti, max. 0.1 wt.% Zn, max. It is a highly formable aluminum alloy containing up to 0.15% by weight of impurities and Al. The microstructure of the aluminum alloy contains at least about 6% volume fraction of beta fibers. In some cases, the volume fraction of alpha fibers in the microstructure of the aluminum alloy is at least about In some cases, the volume fraction and base fraction of alpha fibers in the aluminum alloy may be The volume fraction ratio of the aluminum alloy fibers is about 0.5:1 to 2:1. The aluminum alloy is isotropic. In some cases, the aluminum alloy is constructed with a final gauge thickness of about 0.1 mm to about 3 mm. [Brief description of the drawings]

[0010] [Figure 1A] FIG. 1 is a schematic diagram showing a processing method having a high final cold reduction. [Figure 1B] FIG. 1 is a schematic diagram showing a processing method including coil cooling and having a high final cold reduction. [Diagram 2] FIG. 1 is a schematic diagram illustrating the processing method described herein having a low final cold reduction. [Diagram 3] 1 is a graph illustrating the texture content of aluminum alloys described herein. [Figure 4] 1 is a graph illustrating the yield strength of aluminum alloys described herein. [Diagram 5] 1 is a graph illustrating the ultimate tensile strength of aluminum alloys described herein. [Figure 6] 1 is a graph illustrating uniform elongation of aluminum alloys described herein. [Figure 7]1 is a graph illustrating total elongation of aluminum alloys described herein. [Figure 8] 1 is a graph showing the n-value (i.e., increase in strength after deformation) of aluminum alloys described herein. [Figure 9] 1 is a graph illustrating bulge test deformation of aluminum alloys described herein. [Figure 10] 1 is a graph illustrating r-values ​​for aluminum alloys described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Described herein are methods for making aluminum alloy sheet having an aluminum microstructure that is particularly suitable for producing highly formed aluminum alloy products. The resulting aluminum alloy products have a desired microstructure for limiting plastic anisotropy and improving formability and deep drawability. In some non-limiting examples, the methods for making the highly formable aluminum alloy sheet include a low final cold reduction step that produces a desired crystallographic texture in the microstructure of the aluminum alloy product, e.g., the final gauge aluminum alloy product. In some cases, a low final cold reduction may refer to cold working in which the final cold rolling step, e.g., the last cold rolling step, results in a reduction in gauge thickness of about 70% or less from an intermediate gauge aluminum alloy sheet to a final gauge.

[0012] The methods described herein produce aluminum alloy products with volume fractions of various crystallographic texture components that limit plastic anisotropy. Aluminum alloy products made according to the methods described herein may have a microstructure with a balance of randomly distributed alpha and beta fibers that result in isotropy. Typically, the final cold reduction step reduces the gauge thickness by more than about 70% and causes the alpha fibers, e.g., cube texture components, to align in a linear fashion. The aligned alpha fibers create linearity in the aluminum alloy microstructure, which results in anisotropic behavior. Without being bound to any particular theory, it is believed that the inclusion of a low final cold reduction step results in a balance of randomly distributed texture components, e.g., alpha and beta fibers, that exhibit isotropic behavior. The random distribution of the texture components results in isotropy and formability in all directions. Due to the random distribution of the texture components, the resulting texture components do not align to create linearity that results in anisotropic behavior. The resulting aluminum alloy products exhibit improved quality and consistency in producing highly formed products, as well as being isotropic.

[0013] Aluminum alloys with microstructures having a random distribution of texture constituents improve quality and consistency in the manufacture of complex and highly formed products. The random distribution of texture constituents also tends to improve performance when aluminum and aluminum alloy blanks are formed into finished products. Furthermore, aluminum alloy microstructures having texture constituents with less linearity, e.g., less alignment of cube texture constituents, also improve the formability and performance of aluminum alloy products. Tailored microstructures can be used to improve the formability of aluminum alloy products without reducing strength or weakening the material. In some cases, the highly formable aluminum alloys produced from the methods described herein are particularly In particular, it is useful in the manufacture of aluminum alloys for automotive parts and / or high recycle content.

[0014] Generally, conventional methods for manufacturing aluminum alloy sheets result in, in part, High final cold reduction of the alloy sheet results in a highly oriented microstructure (e.g., one or more For example, an aluminum alloy sheet has a surface that deforms differently depending on the strain direction. Final cold reduction of more than 70%, e.g., 71% to 99%, to obtain a fully recrystallized grain structure. The massive final cold reduction can result in a fibrous structure with alpha fibers that are increasingly straight. This produces an aluminum alloy sheet with anisotropic properties. The inconsistent nature of the aluminum alloy requires additional cutting and machining steps This leads to increased waste and reduced production efficiency. When the r value, which is an index of anisotropy, is close to 0, In this case, the strain is uniform in all directions, so isotropy exists. Therefore, it is necessary to maintain the r value appropriately.

[0015] 1) a low final cold reduction stage, and / or 2) as detailed in the methods herein. Intermediate annealing step (main In the specification, this is also called the inter-annealing step. (which is called "cold reduction") prior to final cold reduction, By properly controlling the process, the crystallographic structure of the aluminum alloy sheet is improved in formability and More specifically, the methods described herein can be optimized to improve the ease of extraction and drawing. The aluminum alloy products obtained from the process are cold-rolled and / or tempered. Compared to the aluminum alloy sheet manufacturing method that does not include a annealing step, the beta fiber is relatively The proportion of alpha fibers with low linearity (e.g., cubic aggregates) is high, while the proportion of alpha fibers with low linearity (e.g., cubic aggregates) is high. The microstructure has alpha and beta fibers within the microstructure. The random distribution of β-sintering results in aluminum alloys with excellent deep drawability and / or high forming limits. These aluminum alloy sheets can be used for automobile parts, etc. Cut.

[0016] In some cases, the combination of the content of alloying elements and the method of preparation and processing of the aluminum alloy sheet. The combination of these produces an aluminum alloy sheet having isotropic properties. The aluminum alloy sheet formed according to the method described herein is preferably made of beta fibers (e.g., yellow fibers). The volume fraction of copper, sulfur, and / or copper is high. In particular, low final cold reduction , limiting the amount of stored energy in the aluminum alloy sheet, which selectively reduces the beta This favors the formation of fibers. In addition, the final cold work reduction is smaller. Due to the reduced amount of stored energy, the alpha fibers become less linear. In alloy sheets, after solution treatment, the beta and alpha fibers (straight lines) are formed. The more the amount of the lattice structure (with reduced lattice properties) formed after solution treatment, the more randomized the microstructure becomes. Fine structures are formed.

[0017] Furthermore, the microstructure of the aluminum resulting from the process described herein is favorable for high final cold reduction. and / or a method for making an aluminum alloy sheet without an intermediate annealing step - Patents.com Compared to , it has a relatively high proportion of beta fibers, which tend to promote high r-values. The aluminum microstructure resulting from the method described herein is created under high final cold reduction. Alpha fibers have a lower linearity compared to alpha fibers. For example, These may refer to texture components that are not aligned in a preferential linear texture arrangement. The improved forming characteristics improve production consistency during forming of the aluminum alloy sheet. This improves the quality and reduces the damage rate of highly formed aluminum products. Improved reliability and efficiency make high speed commercial production more reliable and economically feasible In particular, the aluminum microstructure resulting from the methods described herein is The alloy has a high modulus of ford (quantified by r-value), which is the ratio of thinning in the direction of stress to thinning perpendicular to the direction of stress when the material is under load. Aluminum alloys with high r-values ​​exhibit uniform deformation, e.g., elongation, in all directions, which results in good formability. Additionally, the high r-value of the aluminum alloy indicates that the material is more isotropic and / or less linear. This results in less instability and fewer stress concentrations that can lead to premature failure of the material. The proper balance of the various texture components described herein can reduce the variation in r-values.

[0018] In some cases, the manufacturing method of the aluminum alloy sheet includes an intermediate annealing step, which also contributes to the formation of a random distribution of texture components to limit shear deformation or contributes to a more favorable texture orientation at the same rotation. In other words, the intermediate annealing step creates a balance of alpha and beta fibers without linearity of the preferred texture alignment, which in turn reduces roping in the final product. The reduction in linearity of the texture components in the aluminum alloy microstructure results in an aluminum alloy product with a high r value, which results in an isotropic grain microstructure (low anisotropy).

[0019] Definitions and Explanations As used herein, the terms "invention," "the invention," "this invention," and "the present invention" are intended to refer broadly to all of the subject matter of this patent application and the claims that follow. Statements containing these terms are not intended to limit the subject matter described herein, nor are they intended to limit the meaning or scope of the claims that follow.

[0020] As used herein, the term "alpha fiber" refers to the cube texture component and the Goss texture component.

[0021] As used herein, the term "beta fiber" refers to the brass, S, and copper texture components.

[0022] As used herein, the terms cubic, Goss, rotated Goss, brass, S, and copper refer to different texture components of the microstructure of aluminum alloys. These texture components are known in the art to refer to specific orientations of crystal lattices or polycrystals in Euler space of bulk aluminum alloys, as described by Bunge's rules. Under Bunge's rules, the orientation of crystal lattices or polycrystals in Euler space can be described with respect to three Euler angle (φ1, Φ, φ2) reference axes that represent the following rotations: a first rotation φ1 around the Z axis, a second rotation Φ around the X axis, and a third rotation φ2 around the Z axis. With respect to rolling of metal products, such as sheets or plates, the rolling direction (RD) is parallel to the X axis, the transverse direction (TD) is parallel to the Y axis, and the normal direction (ND) is parallel to the Z axis. Each named texture component may be defined by its specific set of Euler angles (φ1, Φ, φ2) or a range of Euler angles (φ1, Φ, φ2) in Euler space.

[0023] This description refers to alloys identified by aluminum industry designations, e.g., "series" or "6xxx". For an understanding of the numbering systems most commonly used to name and identify aluminum and its alloys, see "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys" or "Registration Record of Aluminum Association Alloy Designations and Chemical Composition Limits", both published by The Aluminum Association. hemical Compositions Limits for Aluminum Alloys in the Form of Castings and Ingo Please refer to "t".

[0024] As used herein, the meanings of "a," "an," or "the" are clear from the context. Singular and plural references are included unless clearly indicated otherwise.

[0025] As used herein, a plate generally has a thickness greater than about 15 mm. For example, the plate may have a thickness of more than about 15 mm, more than about 20 mm, more than about 25 mm, more than about 30 mm, or Al over 35mm, over about 40mm, over about 45mm, over about 50mm, or over about 100mm This may refer to minium products.

[0026] As used herein, a shate (also called a sheet plate) is a Generally, the thickness is about 4 mm to about 15 mm. For example, the shade has a thickness of about 4 mm and a width of about 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 11mm, 12m m, about 13 mm, about 14 mm, or about 15 mm.

[0027] As used herein, a sheet generally has a thickness of less than about 4 mm (e.g., less than 3 mm, Less than 2mm, less than 1mm, less than 0.5mm, less than 0.3mm, or less than 0.1mm) For example, sheets are aluminum products with a thickness of about 0.1 mm, about 0.2 mm, Approx. 0.3mm, approx. 0.4mm, approx. 0.5, approx. 0.6mm, approx. 0.7mm, approx. 0.8mm, Approx. 0.9mm, approx. 1mm, approx. 1.1mm, approx. 1.2mm, approx. 1.3mm, approx. 1.4mm, Approximately 1.5mm, approximately 1.6mm, approximately 1.7mm, approximately 1.8mm, approximately 1.9mm, approximately 2mm, Approx. 2.1mm, approx. 2.2mm, approx. 2.3mm, approx. 2.4mm, approx. 2.5mm, approx. 2.6m m, approx. 2.7mm, approx. 2.8mm, approx. 2.9mm, approx. 3mm, approx. 3.1mm, approx. 3.2m m, approx. 3.3mm, approx. 3.4mm, approx. 3.5mm, approx. 3.6mm, approx. 3.7mm, approx. 3. 8 mm, or about 3.9 mm.

[0028] As used herein, formability refers to the ability of a material to withstand breakage, cutting, necking, edge cracking, etc. or forming errors, such as shrinkage, springback, or wear, can be achieved without It refers to the ability of a material to be deformed into a shape. In engineering, formability can be classified according to the deformation mode. Examples of deformation modes include drawing, stretching, bending, and stretch flanging. do.

[0029] In this application, alloy tempers or conditions are discussed. The most commonly used alloy tempers are For information on understanding quality statements, see the American National Standards s(ANSI)H35 on Alloy and Temper Designati F state or temper is the as-manufactured aluminum alloy. Refers to aluminum alloys in the O condition or tempered state. O condition or temper refers to aluminum alloys after they have been annealed. T1 condition or temper refers to a material that has been naturally aged (e.g., at room temperature) after cooling from hot working. Refers to aluminum alloys in the T2 condition or temper, which are hot worked, cooled, and then cold worked. T3 condition or temper refers to an aluminum alloy that has been solution-treated and then naturally aged. Refers to an aluminum alloy that has been cold worked and naturally aged. The T4 condition or temper refers to a solution-treated Refers to aluminum alloys that have been naturally aged after processing. T5 condition or temper refers to alloys that have been hot worked or Refers to an aluminum alloy that has been artificially aged (e.g., at high temperature) after cooling from the T6 condition. or tempered refers to aluminum alloys that have been solution-treated and then artificially aged. T7 condition or Tempered refers to aluminum alloys that have been artificially overaged after solution treatment. "T9" refers to an aluminum alloy that has been solution-treated, cold-worked, and artificially aged. The condition or temper is an aluminum alloy that has been solution treated, artificially aged, and then cold worked. W condition or temper refers to aluminum alloys after solution treatment.

[0030] As used herein, "room temperature" includes temperatures from about 15°C to about 30°C, e.g., about 15°C, about 16°C, about 17°C, about 18°C, about 19°C, about 20°C, about 21°C, about 22°C, about 23°C, about 24°C, about 25°C, about 26°C, about 27°C, about 28°C, about 29°C, or about 30°C.

[0031] As used herein, the terms "cast aluminum alloy product," "cast metal product," "cast product," and the like are synonymous and refer to products produced by direct chill casting (including direct chill co-casting) or semi-continuous casting, continuous casting (including, for example, twin belt caster, twin roll caster, block caster, or any other continuous casting machine), electromagnetic casting, hot top casting, or any other casting process, or any combination thereof.

[0032] All ranges disclosed herein should be understood to encompass the endpoints and all subranges subsumed therein. For example, a range stated as "1 to 10" should be considered to include all subranges between (and including) the minimum value of 1 and the maximum value of 10, i.e., all subranges beginning with a minimum value of 1 or more, e.g., 1 to 6.1, and ending with a maximum value of 10 or less, e.g., 5.5 to 10.

[0033] The following aluminum alloys are listed in terms of elemental composition in weight percent (wt%) based on the total weight of the alloy, with the balance being aluminum and the maximum wt% of the sum of impurities being 0.15% in certain examples of each alloy.

[0034] Manufacturing method of aluminum alloy products Described herein are novel methods for making aluminum alloy products that exhibit desired mechanical properties. Among other properties, the methods for making aluminum alloys described herein result in aluminum alloy products that exhibit excellent elongation and formability properties. In some cases, the mechanical properties can be achieved by processing the aluminum alloy. For example, the processing methods described further herein include a low final cold reduction step, e.g., a cold work reduction of about 70% or less, and an optional intermediate annealing (i.e., inter-annealing) step. In some examples, a low final cold reduction may refer to cold working that reduces the gauge thickness of the aluminum alloy product by less than about 40% to about 70% in a final cold rolling step, e.g., the last cold rolling step. The low final cold reduction step and / or the intermediate annealing step result in an aluminum alloy microstructure with a more randomized texture, e.g., a random distribution of alpha and beta fibers. Furthermore, the low final cold reduction step and / or intermediate annealing step reduces the linearity of the texture components, e.g., the aligned cube texture components, resulting in an aluminum alloy product with a high r value. The balance of alpha and beta fibers in turn provides a more randomized microstructure, which in turn results in an aluminum alloy product with isotropic properties. The resulting aluminum alloy product exhibits desired forming properties. In certain embodiments, the method of making and processing the aluminum alloy product may affect or even determine whether the product has suitable properties for a desired application.

[0035] Certain aspects and features of the present disclosure relate to the crystallographic texture and / or microstructure of aluminum alloys that are particularly suitable for producing highly formable products. The crystallographic texture of the aluminum alloy product (e.g., sheet), including the specific volume fractions of the texture components and the ratios of different fibers in the alloy microstructure, affects the formability of the aluminum alloy product when it is processed into a finished product. Aluminum alloys having the crystallographic texture described herein exhibit isotropy, resulting in more uniform deformation of the aluminum alloy sheet.

[0036] casting As further described herein, the aluminum alloy can be cast using any suitable casting method. The casting process may be performed using a direct chill (DC) process to produce cast aluminum alloy products. In some non-limiting examples, the casting process may include a casting or continuous casting (CC) process. The aluminum alloys for use in the step are prepared from raw materials (e.g., refined aluminum and In some further examples, the casting may be made from a raw material made from a metal such as copper, copper alloy, or copper alloying elements. The aluminium alloy for use in the step is at least partially made of aluminium waste and Optionally, the raw material may be a recycled material produced by combining with the raw material. Aluminum alloys for use in flooring may contain at least about 40% recycled content. For example, the aluminum alloy for use in the casting step may be at least about 45% At least about 50%, at least about 60%, at least about 70%, at least about 80%, The regenerated content may be about 90%, or at least about 95%.

[0037] The cast aluminum alloy product may then be subjected to further processing steps. The processing methods described in the specification include homogenization, hot rolling, cold rolling, and the like to obtain aluminum alloy products. The process may include steps of rolling, rolling, and / or solution treatment.

[0038] Homogenization The homogenization step described herein was designed for the aluminum alloys described herein. The homogenization step is carried out at a temperature of about 450 to about 600° C. (e.g., about 450° C., about 460° C., about 470° C. , about 480°C, about 490°C, about 500°C, about 510°C, about 520°C, about 530°C, about 54 0°C, about 550°C, about 560°C, about 570°C, about 580°C, about 590°C, or about 600°C The method may include heating the cast aluminum alloy to reach a temperature of 100° C. For example, the cast aluminum alloy is heated at about 500°C to about 570°C or about 530°C to about 570°C. In some embodiments, the heating of the cast aluminum alloy may be performed up to a temperature of Approximately 15 hours (for example, about 20 minutes to about 15 hours or about 5 hours to about 10 hours, all included) For example, the cast aluminum alloy is heated to a temperature of about 450°C to about 600°C for about 2 0 minutes, about 30 minutes, about 45 minutes, about 1 hour, about 1.5 hours, about 2 hours, about 3 hours, about 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours Cook for about 13 hours, about 14 hours, or about 15 hours, or any time therebetween. It is possible.

[0039] In some cases, the heating rate is about 100° C. / hour or less, 75° C. / hour or less, 50° C. / hour or less. below, 40℃ / hour or less, 30℃ / hour or less, 25℃ / hour or less, 20℃ / hour or less, or 15℃ In other cases, the heating rate can be from about 10° C. / min to about 100° C. / min (e.g., For example, about 10°C / min to about 90°C / min, about 10°C / min to about 70°C / min, about 10°C / min to about 6 0℃ / min, approx. 20℃ / min to approx. 90℃ / min, approx. 30℃ / min to approx. 80℃ / min, approx. 40℃ / min to The heating rate may be about 70° C. / min, or about 50° C. / min to about 60° C. / min.

[0040] The cast aluminum alloy is then soaked for a period of time (i.e., at the indicated temperature). According to one non-limiting example, the cast aluminum alloy may be heated to a temperature of up to about 1 5 hours (for example, about 20 minutes to about 15 hours or about 5 hours to about 10 hours, all inclusive) For example, the cast aluminum alloy is heated at a temperature of about 450°C to about 600°C. 20 minutes, 30 minutes, 45 minutes, 1 hour, 1.5 hours, 2 hours, 3 hours, 4 hours 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, about 13 hours, about 14 hours, or about 15 hours, or any time therebetween It may be soaked.

[0041] Hot rolling The homogenization step may be followed by a hot rolling step. In some cases, the cast aluminum alloy product is laid down and hot rolled at an inlet temperature range of about 500°C to about 560°C (e.g., about 510°C to about 550°C or about 520°C to about 540°C). The inlet temperature may be, for example, about 505°C, 510°C, 515°C, 520°C, 525°C, 530°C, 535°C, 540°C, 545°C, 550°C, 555°C, 560°C, or anything in between. In some cases, the hot rolling outlet temperature may be about 200°C to about 290°C (e.g., about 210°C to about 280°C or about 220°C to about 270°C). For example, the hot rolling exit temperature can be about 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, or anything in between.

[0042] In some cases, the cast aluminum alloy product is hot rolled to about 4 mm to about 15 mm gauge (eg, about 5 mm to about 12 mm gauge) and is referred to as a hot rolled product. For example, the castings may be hot rolled to 15 mm gauge, 14 mm gauge, 13 mm gauge, 12 mm gauge, 11 mm gauge, 10 mm gauge, 9 mm gauge, 8 mm gauge, 7 mm gauge, 6 mm gauge, 5 mm gauge, or 4 mm gauge. The temper of the as-rolled hot rolled product is referred to as the F temper.

[0043] Coil Cooling Optionally, the hot rolled product may be coiled upon exiting the hot rolling mill into a hot rolled coil (i.e., an intermediate gauge aluminum alloy product coil or intermediate coil). In some examples, the hot rolled product is coiled into a hot rolled coil upon exiting the hot rolling mill and is F tempered. In some further examples, the hot rolled product is cooled, e.g., air cooled. The cooling step can occur at a rate of about 12.5°C / hour (°C / h) to about 3600°C / h. For example, the coil cooling step can occur at a rate of about 12.5°C / h, 25°C / h, 50°C / h, 100°C / h, 200°C / h, 400°C / h, 800°C / h, 1600°C / h, 3200°C / h, 3600°C / h, or any rate in between. In some further examples, the cooling coil is stored for a period of time. In some examples, the intermediate coil is maintained at a temperature of about 100°C to about 350°C (e.g., about 200°C or about 300°C).

[0044] Cold rolling The hot rolling step may be followed by a cold rolling step. In some examples, the cold rolling step is a two-stage cold rolling step. The two-stage cold rolling step may include a first cold rolling step, an optional intermediate annealing step, and a second cold rolling step. Optionally, the method may further include annealing the rolled product after the second cold rolling step. In certain embodiments, the hot rolled product may be cold rolled to an intermediate gauge thickness in a first cold rolling step, i.e., a first cold rolled product. In some examples, the first cold rolling step reduces the thickness of the hot rolled product by about 30% to 70% (e.g., about 30% to about 65%, about 35% to about 65%, about 45% to about 60%, or about 50% to about 60%). For example, the first cold rolling step reduces the thickness of the hot rolled product by about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, or about 70%.

[0045] In certain embodiments, the hot rolled product is cold rolled in the first cold rolling stage to an intermediate gauge aluminum alloy product (e.g., sheet or sheet). In some examples, the intermediate gauge aluminum alloy product is between about 2 mm and 6 mm (e.g., between about 2.2 mm and about 5.8 mm, between about 2.4 mm and about 5.6 mm, between about 2.6 mm and about 5.4 mm, Approx. 2.8mm to 5.2mm, Approx. 3mm to 5mm, Approx. 3.2mm to 4.8mm, Approx. .4mm~4.6mm, 3.6mm~4.4mm, 3.8mm~4.2mm, Thickness: about 4mm to about 5mm, about 2.5mm to about 3.5mm, or about 3mm to about 4mm In some examples, the medium gauge aluminum alloy product has a gauge of about 6 mm or less. Approx. 5.8mm or less, approx. 5.6mm or less, approx. 5.4mm or less, approx. 5.2mm or less, approx. 5mm Below, about 4.8mm or less, about 4.6mm or less, about 4.4mm or less, about 4.2mm or less, about 4mm or less, approximately 3.9mm or less, approximately 3.8mm or less, approximately 3.7mm or less, approximately 3.6mm or less Below, approximately 3.5mm or less, approximately 3.4mm or less, approximately 3.3mm or less, approximately 3.2mm or less, and has a thickness of about 3.1 mm or less.

[0046] A second cold rolling step may be performed on the intermediate gauge aluminium alloy product. In certain embodiments, the second cold rolling step is preceded by an optional intermediate annealing step (described below). In some instances, the second cold rolling step may be performed after the first cold rolling step. The total thickness of the product is about 50 to 70% (for example, about 50% to about 60%, about 55% to about 65%, about 6 The concentration is reduced by about 0% to about 70%, about 65% to about 70%, or about 60% to 65%). For example, The second cold rolling step reduces the thickness of the first cold rolled product by an additional 50%, about 51%. %, approx. 52%, approx. 53%, approx. 54%, approx. 55%, approx. 56%, approx. 57%, approx. 58%, approx. 59 %, approx. 60%, approx. 61%, approx. 62%, approx. 63%, approx. 64%, approx. 65%, approx. 66%, approx. 67 %, about 68%, about 69%, or about 70%.

[0047] In certain embodiments, the intermediate gauge aluminum alloy product is a final gauge aluminum alloy product. cold rolled into aluminum alloy products (e.g., sheets, e.g., lower gauge sheets) In some instances, the final gauge aluminum alloy product may have a thickness of about 0.1 mm to 3 mm ( For example, about 0.2 mm to about 2.9 mm, about 0.3 mm to about 2.8 mm, about 0.4 mm to about 2.7mm, about 0.5mm to about 2.6mm, about 0.6mm to about 2.5mm, about 0.7mm ~2.4mm, approximately 0.8mm~2.3mm, approximately 0.9mm~2.2mm, approximately 1mm ~2.1mm, 1.1mm~2.0mm, 1.2mm~1.9mm, 1.3mm mm to 1.8 mm, 1.4 mm to 1.7 mm, or 1.5 mm to 1.6 mm In some examples, the final gauge aluminum alloy product has a thickness of about 3 mm. m or less, approximately 2.8 mm or less, approximately 2.6 mm or less, approximately 2.4 mm or less, approximately 2.2 mm or less, Approx. 2mm or less, approx. 1.8mm or less, approx. 1.6mm or less, approx. 1.4mm or less, approx. 1.2mm Below, about 1mm or less, about 0.9mm or less, about 0.8mm or less, about 0.7mm or less, about 0. 6mm or less, approximately 0.5mm or less, approximately 0.4mm or less, approximately 0.3mm or less, or approximately 0.2 It has a thickness of less than mm.

[0048] The method of making an aluminum alloy sheet as described herein comprises a low final cold reduction step, This produces a desired crystallographic texture in the microstructure of the aluminum alloy product. In some cases, a low final cold reduction is used in the final cold rolling stage, e.g., the last cold rolling stage. At this stage, the reduction in gauge thickness from intermediate gauge aluminum alloy sheet to final gauge is approximately It can also refer to cold working to a temperature of 70% or less. For example, medium gauge aluminum alloys After the first cold rolling step to produce the intermediate gauge aluminum alloy product, the gauge of the intermediate gauge aluminum alloy product is In the final cold rolling stage, the temperature is reduced by about 70% or less. The second cold rolling step is the final cold reduction step of 70% or less. This results in a higher final cold reduction ratio compared to the beta and alpha fibers (less linear). Thus, an aluminum alloy product is produced having a balanced volume fraction of 0.1% to 1.0% of the aluminum alloy.

[0049] The low final cold reduction reduces the average r-value of the aluminum alloy sheet product by a factor of 10 to 15. Improved compared to aluminum alloys made under and / or without intermediate annealing. This in turn improves moldability in complex and highly molded products. The aluminum alloy sheet produced according to the method has a higher total volume fraction of alpha fibers (with reduced linearity) and beta fibers than aluminum alloy sheets having a high final cold reduction (e.g., greater than 70% final cold reduction). By controlling the processing conditions for producing the aluminum alloy sheet, a desired aluminum alloy microstructure having a random distribution of alpha and beta fibers is achieved. Furthermore, the higher volume fraction of beta fibers resulting after solution treatment results in a more randomized microstructure in the aluminum alloy sheet, which contributes to the production of an isotropic alloy microstructure.

[0050] Optional intermediate annealing In some non-limiting examples, an optional intermediate annealing step can be performed between the two cold rolling steps. For example, the hot rolled product can be cold rolled to an intermediate gauge aluminum alloy product (first cold rolling step), optionally coiled, annealed, and then cold rolled to a final gauge aluminum alloy product (second cold rolling step). In some embodiments, the optional intermediate annealing can be performed in a batch process (i.e., a batch intermediate annealing step) or a continuous process. The intermediate annealing step can be performed at a temperature of about 300°C to about 450°C (e.g., about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, about 400°C, about 410°C, about 420°C, about 430°C, about 440°C, or about 450°C).

[0051] In some cases, the heating rate of the intermediate annealing step can be about 100° C. / hr or less, 75° C. / hr or less, 50° C. / hr or less, 40° C. / hr or less, 30° C. / hr or less, 25° C. / hr or less, 20° C. / hr or less, or 15° C. / hr or less. In other cases, the heating rate can be about 10° C. / min to about 100° C. / min (e.g., about 10° C. / min to about 90° C. / min, about 10° C. / min to about 70° C. / min, about 10° C. / min to about 60° C. / min, about 20° C. / min to about 90° C. / min, about 30° C. / min to about 80° C. / min, about 40° C. / min to about 70° C. / min, or about 50° C. / min to about 60° C. / min).

[0052] In some embodiments, the intermediate gauge aluminum alloy product is soaked for a period of time during the intermediate annealing step. According to one non-limiting example, the intermediate gauge aluminum alloy product is soaked for up to about 5 hours (e.g., about 30 minutes to about 4 hours, about 45 minutes to about 3 hours, or about 1 hour to about 2 hours, inclusive). For example, the intermediate gauge aluminum alloy product may be soaked at a temperature of about 300°C to about 450°C for about 20 minutes, about 30 minutes, about 45 minutes, about 1 hour, about 1.5 hours, about 2 hours, about 3 hours, about 4 hours, about 5 hours, or any time therebetween.

[0053] Optionally, the intermediate gauge aluminum alloy product may be cooled, e.g., air cooled, after the intermediate annealing step. The cooling step may be performed at a rate of about 5°C / hour (°C / h) to 20°C / hour (e.g., 6°C / h to 18°C / h, 8°C / h to 15°C / h, or 10°C / h to 14°C / h). For example, the coil cooling step may be performed at about 5°C / h, 6°C / h, 7°C / h, 8°C / h, 9°C / h, 10°C / h, 11°C / h, 12°C / h, 13°C / h, 14°C / h, 15°C / h, 16°C / h, 17°C / h, 18°C / h, 19°C / h, 20°C / h, or any rate in between. In some examples, the cooling coil is cooled to room temperature. In some further examples, the cooling coil is stored for a period of time.

[0054] The optional intermediate annealing step can also improve the average r-value of the aluminum sheet product. The intermediate annealing step also contributes to creating a more random distribution of texture components in the aluminum alloy microstructure to limit shear deformation, which in turn reduces the linearity of the texture components (e.g., less linear cube texture components) and prevents roping in the final product. The random distribution of texture components results in a higher r-value. For example, the r-value at an angle (e.g., 45°) to the rolling direction can be at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.8, or at least 0.9. The higher r-value can be achieved by reducing the linearity of the texture components in the aluminum alloy microstructure. The isotropic behavior of the sheet is shown.

[0055] Solution Treatment A solution treatment step may optionally be performed on the final gauge aluminum alloy product. The annealing step heats the final gauge aluminum alloy product from room temperature to the maximum temperature of the metal. Optionally, the maximum temperature of the metal may be from about 530° C. to about 570° C. (e.g. , about 535°C to about 560°C, about 545°C to about 555°C, or about 540°C). The final gauge aluminum alloy product is soaked for a period of time at the maximum temperature of the metal. In certain embodiments, the final gauge aluminum alloy product may have a maximum of about 2 The soaking time can be from about 10 seconds to about 120 seconds, inclusive. For example, the final gauge aluminum alloy product is annealed at a temperature of about 530°C to about 570°C for 10 seconds. , 15 seconds, 20 seconds, 25 seconds, 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, 60 seconds , 65 seconds, 70 seconds, 75 seconds, 80 seconds, 85 seconds, 90 seconds, 95 seconds, 100 seconds, 105 seconds, 1 The soaking may be for 10 seconds, 115 seconds, 120 seconds, or any time in between. After processing, the final gauge aluminum alloy product is at least about 100°C from the maximum temperature of the metal. For example, the final gauge aluminum alloy may be quenched at a rate of 75° C. per second (° C. / sec). The product is approximately 75℃ / sec, 100℃ / sec, 125℃ / sec, 150℃ / sec, 175℃ / sec, 2 00° C. / sec, or any rate in between.

[0056] Optionally, the aluminum alloy product may then be naturally and / or artificially aged. In some non-limiting examples, the aluminum alloy product is heated at room temperature (e.g., about 15° C., Storage at approximately 20°C, approximately 25°C, or approximately 30°C for at least 72 hours results in T4 The aluminum alloy product may be naturally aged to temper. For example, the aluminum alloy product may be aged for 72 hours, 84 hours, 96 hours, 108 hours, 120 hours, 132 hours, 144 hours, 156 hours, 168 hours , 180 hours, 192 hours, 204 hours, 216 hours, 240 hours, 264 hours, 288 hours hours, 312 hours, 336 hours, 360 hours, 384 hours, 408 hours, 432 hours, 4 56 hours, 480 hours, 504 hours, 528 hours, 552 hours, 576 hours, 600 hours , 624 hours, 648 hours, 672 hours, or any period therebetween. .

[0057] Microstructure The aluminum alloy products produced from the methods described herein have multiple crystallographic structure components. The crystallographic texture component includes a microstructure having an alpha fiber (e.g., a cubic component). and Goss components) and beta fibers (e.g., brass components, S components, and copper components). For example, the methods described herein can improve quality and consistency in the production of highly molded products. Improved linearity of the beta fibers and the alpha fibers, which are isotropic, is shown. This results in an aluminum microstructure with a high volume fraction of

[0058] In some instances, the microstructure of the aluminum alloy may include alpha fibers, e.g., one or more Optionally, the aluminum alloy may include a cubic component and a Goss component in the microstructure. The volume fraction of alpha fibers in the fiber is at least about 8% (e.g., at least about 9%, at least about 10%, at least about 11%, at least about 12%, at least about 13%, at least In some examples, the aluminum content may be at least about 14%, or at least about 15%. The volume fraction of alpha fibers in the microstructure of aluminum alloys is up to about 20% (e.g., up to about 1 8%, up to about 16%, up to about 15%, up to about 14%, up to about 12%, or up to about 10% For example, the volume fraction of alpha fibers in the microstructure of the aluminum alloy is About 0.1%, for example, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8% ,4.9%,5.0%,5.1%,5.2%,5.3%,5.4%,5.5%,5.6%,5.7%,5.8%,5.9%,6.0%,6.1%,6.2%,6.3%,6.4%,6.5%,6.6%,6.7%,6.8%,6.9%,7.0%,7.1%,7.2%,7.3%, %, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8.0%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9.0%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9. 8%, 9.9%, 10.0%, 10.1%, 10.2%, 10.3%, 10.4%, 10.5%, 10.6%, 10.7%, 10.8%, 10.9%, 11.0%, 11.1%, 11.2%, 11.3%, 11.4%, 11.5%, 11.6%, 11.7%, 11.8%, 11. 9%, 12.0%, 12.1%, 12.2%, 12.3%, 12.4%, 12.5%, 12.6%, 12.7%, 12.8%, 12.9%, 13.0%, 13.1%, 13.2%, 13.3%, 13.4%, 13.5%, 13.6%, 13.7%, 13.8%, 13.9%, 1 4.0%, 14.1%, 14.2%, 14.3%, 14.4%, 14.5%, 14.6%, 14.7%, 14.8%, 14.9%, 15.0%, 15.1%, 15.2%, 15.3%, 15.4%, 15.5%, 15.6%, 15.7%, 15.8%, 15.9%, 16.0% , 16.1%, 16.2%, 16.3%, 16.4%, 16.5%, 16.6%, 16.7%, 16.8%, 16.9%, 17.0%, 17.1%, 17.2%, 17.3%, 17.4%, 17.5%, 17.6%, 17.7%, 17.8%, 17.9%, 18.0%, 18.1%, 18.2%, 18.3%, 18.4%, 18.5%, 18.6%, 18.7%, 18.8%, 18.9%, 19.0%, 19.1%, 19.2%, 19.3%, 19.4%, 19.5%, 19.6%, 19.7%, 19.8%, 19.9%, or 20.0%.

[0059] In some examples, the microstructure of the aluminum alloy can include beta fibers, such as one or more of a brass component, a S component, and a copper component. Optionally, the volume fraction of the beta fibers can be at least about 6% (e.g., at least about 6%, at least about 7%, at least about 8%, at least about 9%, at least about 10%, at least about 11%, at least about 12%, at least about 13%, at least about 14%, or at least 15%). In some examples, the volume fraction of the beta fibers is up to about 20% (e.g., up to about 15% or up to about 10%). For example, the volume fraction of beta fibers in the microstructure of the aluminum alloy may be about 0.1%, e.g., 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%. ,3.1%,3.2%,3.3%,3.4%,3.5%,3.6%,3.7%,3.8%,3.9%,4.0%,4.1%,4.2%,4.3%,4.4%,4.5%,4.6%,4.7%,4.8%,4.9%,5.0%,5.1%,5.2%,5.3%,5.4%,5.5%,5.6%,5.7%,5.8%,5.9%,6.0%,6.1%,6.2%,6.3%,6.4%,6.5%,6.6%,6.7%,6. 8%, 6.9%, 7.0%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8.0%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9.0%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10.0%, 10.1%, 10.2%, 10.3%, 10.4%, 10.5%, 10.6%, 10.7%, 10.8%, 10.9%, 11.0%, 11.1%, 11.2%, 11.3%, 11.4%, 11.5%, 11.6%, 11.7%, 11.8%, 11.9%, 12.0%, 12.1%, 12.2%, 12.3%, 12.4%, 12.5%, 12.6%, 12.7%, 12.8%, 12.9%, 13.0%, 13.1%, 13.2%, 13.3%, 13.4%, 13.5%, 13.6%, 13.7%, 13.8%, 13.9%, 14.0%, 14.1%, 14.2%, 14.3%, 14.4%, 14.5%, 14.6%, 14.7%, 14.8%, 14.9 ...7%, 14.8%, 14.9%, 14.1%, 14.1%, 14.2%, 14.3%, 14.4%, .6%, 13.7%, 13.8%, 13.9%, 14.0%, 14.1%, 14.2%, 14.3%, 14.4%, 14.5%, 14.6%, 14.7%, 14.8%, 14.9 %, 15.0%, 15.1%, 15.2%, 15.3%, 15.4%, 15.5%, 15 .6%, 15.7%, 15.8%, 15.9%, 16.0%, 16.1%, 16.2%, 16.3%, 16.4%, 16.5%, 16.6%, 16.7%, 16.8%, 16.9 %, 17.0%, 17.1%, 17.2%, 17.3%, 17.4%, 17.5%, 17 .6%, 17.7%, 17.8%, 17.9%, 18.0%, 18.1%, 18.2%, 18.3%, 18.4%, 18.5%, 18.6%, 18.7%, 18.8%, 18.9 %, 19.0%, 19.1%, 19.2%, 19.3%, 19.4%, 19.5%, 19 It could be .6%, 19.7%, 19.8%, 19.9%, or 20.0%.

[0060] Aluminum alloys having a microstructure with a relatively high proportion of beta fibers have been shown to exhibit improved formability. The alpha fibers exhibit reduced linearity and can be molded into complex, highly shaped products. Aluminum alloys having microstructures with a relatively high proportion of Cr, similarly, are subject to high final cold reductions. and / or compared to methods of producing aluminum alloys that do not include an intermediate annealing step. The resulting higher proportion of alpha fibers (straightness) can improve moldability. The aluminum alloy brazes are made of beta fibers, which reduce the strength of the finished product. There is also a trend towards improved ink performance.

[0061] In some cases, the volume fraction of alpha fibers and the volume fraction of beta fibers in the aluminum alloy product The volume fraction ratio is about 0.5:1 to 2:1 (e.g., about 0.6:1 to 1.9:1, about 0.6 :1~1.8:1, approx. 0.7:1~1.7:1, approx. 0.8:1~1.6:1, approx. 0.9: 1~1.5:1, about 1:1~1.4:1, about 1.1:1~1.3:1, or about 1.2: In some examples, the alpha fiber in the aluminum alloy product may be The ratio of the volume fraction of the β-fibers to the volume fraction of the β-fibers is at least about 0.5:1, 0.6:1, 0. 7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1. 4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, or 2:1 It is.

[0062] The microstructure of the aluminum alloy disclosed herein is a complex fabrication process for aluminum alloy sheets. Facilitates shaping and forming into products. The microstructure of the aluminum alloy with beta and alpha fibers distributed in the dam is highly Demonstrates improved quality and consistency in the manufacture of molded products. For example, alpha fiber (straight The higher the proportion of beta fibers, the higher the aluminum or aluminum alloy. The formability of the gold is improved and the distortion of the aluminum throughout the manufacturing process is reduced. The microstructure is made by various shaping and forming processes. This can improve efficiency, production speed of minium products and reduce spoilage rates.

[0063] The aluminum alloy has a large amount of beta fibers in its microstructure and has reduced linearity of alpha fibers. The fiber fibers help improve moldability. The proper combination of the various texture components described herein Depending on the alignment, the rolling method of the metal sheet, plate, or sheath may be adjusted to 0° to 90°. The variation of the Lankford parameter, or r-value, of the grains at 100° is reduced. The right combination of components improves manufacturing consistency and reduces forming time for highly formed aluminum products. Therefore, by controlling the volume fraction of different texture components, , the anisotropic forming behavior of the metal for a particular processing method or part geometry may be reduced.

[0064] The microstructures and their associated texture constituents disclosed herein allow the aluminum alloy to have complex streaks. The microstructure of the metal allows it to deform in a specific direction more favorably under the strain path. The structure and / or grains then react to stresses applied from different directions and / or orientations. For example, elongation may not be the same when the aluminum alloy grains are deformed in the rolling direction (0°) compared to the transverse direction (90°). This difference in behavior is due to the difference in the crystallographic orientation of the grains (i.e., microstructure). As the grains are oriented differently throughout the microstructure, different crystallographic slip systems, which may consist of various combinations of slip planes and / or slip directions, affect the overall deformation. New dislocations may be generated so that the grains collectively accommodate the strain and / or deformation without losing continuity. These dislocations may only move the crystals in certain directions on certain slip planes. If the number of available slip planes is low, the material's ability to strain is reduced. Conversely, if the number of active slip planes is high, the material's ability to strain is increased. Therefore, by controlling the volume fractions of the different texture components, the anisotropic forming behavior of the metal for a particular processing method or part geometry can be reduced.

[0065] In some cases, final gauge aluminum alloy products produced according to the processes described herein have higher yield strengths, ultimate tensile strengths, uniform elongations, and total elongations than aluminum alloys produced by high final cold reductions and / or processes that do not include an intermediate annealing step. The aluminum alloy products described herein may exhibit yield strengths and ultimate tensile strengths as described herein when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions, respectively, relative to the rolling direction. In some embodiments, the final gauge aluminum alloy product produced according to the methods described herein has a yield strength that is at least about 6% greater (e.g., at least 7% greater, at least 8% greater, at least 9% greater, at least 10% greater, at least 11% greater, at least 12% greater, at least 13% greater, at least 14% greater, at least 15% greater, at least 16% greater, at least 17% greater, at least 18% greater, or at least 19% greater) than the yield strength of an aluminum alloy produced by a method that includes a final cold rolling step in which the thickness reduction from the intermediate gauge aluminum alloy to the final gauge aluminum alloy is greater than 70%. In some cases, the final gauge aluminum alloy product has an ultimate tensile strength that is at least about 3% greater (e.g., at least 4% greater, at least 5% greater, at least 6% greater, at least 7% greater, at least 8% greater, at least 9% greater, at least 10% greater, at least 11% greater, at least 12% greater, at least 13% greater, at least 14% greater, or at least 15% greater) than an ultimate tensile strength of an aluminum alloy produced by a process that includes a final cold rolling step in which the thickness reduction from the intermediate gauge aluminum alloy to the final gauge aluminum alloy exceeds 70%.

[0066] The aluminum alloy products described herein may exhibit uniform and total elongation as described herein when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions, respectively, relative to the rolling direction. In some cases, the final gauge aluminum alloy products have a total elongation that is at least about 5% greater (e.g., at least 6% greater, at least 7% greater, at least 8% greater, at least 9% greater, at least 10% greater, at least 11% greater, at least 12% greater, at least 13% greater, at least 14% greater, at least 15% greater, at least 16% greater, at least 17% greater, at least 18% greater, or at least 19% greater) than the total elongation of an aluminum alloy produced by a process that includes a final cold rolling step in which the thickness reduction from the intermediate gauge aluminum alloy to the final gauge aluminum alloy exceeds 70%. In some cases, the final gauge aluminum alloy product has a uniform elongation that is at least about 3% greater (e.g., at least 4% greater, at least 5% greater, at least 6% greater, at least 7% greater, at least 8% greater, at least 9% greater, at least 10% greater, at least 11% greater, at least 12% greater, at least 13% greater, at least 14% greater, at least 15% greater, at least 16% greater) than the uniform elongation of an aluminum alloy produced by a process that includes a final cold rolling step in which the reduction in thickness from the intermediate gauge aluminum alloy to the final gauge aluminum alloy exceeds 70%. or at least 17% greater).

[0067] Alloy composition The properties of an aluminum alloy are determined in part by the composition of the aluminum alloy. In certain embodiments, the alloy composition is selected so that the alloy has suitable properties for a desired application, e.g., molding, In some cases, this can affect or even determine whether a material has good mechanical and deep drawability. Among other properties, the aluminum alloys described herein have excellent elongation and formability properties. Indicates gender.

[0068] In some cases, the aluminum alloys described herein have an elemental composition as shown in Table 1 below. It is possible. Table 1 JPEG2025032283000002.jpg74170

[0069] In some examples, the aluminum alloys described herein have an elemental composition as shown in Table 2 below. may have: Table 2 JPEG2025032283000003.jpg74150

[0070] In some examples, the aluminum alloys described herein have an elemental composition as shown in Table 3 below. may have: Table 3 JPEG2025032283000004.jpg74150

[0071] In some examples, the aluminum alloys described herein include about 0.5% to about 2.0% (e.g., about 0.7 to about 1.5% or about 1.0 to about 1.4%) silicon (Si) based on the total weight of the alloy.For example, the alloy may contain 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.6%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.7%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.8%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0. 86%, 0.87%, 0.88%, 0.89%, 0.9%, 0.9%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.0%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.1%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, 1.2%, 1.21%, 1.22%, 1.23%, 1.24%, 1.25%, 1.26%, 1.27%, 1.28%, 1.29%, 1.3%, 1.31%, 1.32%, 1.33%, 1.34%, 1.35%, 1.36%, 1.37%, 1.38%, 1.39%, 1.4%, 1.41%, 1.42%, 1.43%, 1.44%, 1.45%, 1.46%, 1.47%, 1.48%, 1.49%, 1.5%, 1.51%, 1.52%, 1.53%, 1.54%, 1.55%, 1.56%, 1.57%, 1.58%, 1.59%, 1.6%, 1.61%, 1.62%, 1.6 3%, 1.64%, 1.65%, 1.66%, 1.67%, 1.68%, 1.69%, 1.7%, 1.71%, 1.72%, 1.73%, 1.74%, 1.75%, 1.76%, 1.77%, 1.78%, 1.79%, 1.8%, 1.81%, 1.82%, 1.83%, 1.84%, 1.85%, 1.86%, 1.87%, 1.88%, 1.89%, 1.9%, 1.91%, 1.92%, 1.93%, 1.94%, 1.95%, 1.96%, 1.97%, 1.98%, 1.99%, or 2.0%, all by weight.

[0072] In some examples, the aluminum alloys described herein include about 0.05% to about 0.40% iron (Fe) based on the total weight of the alloy (e.g., about 0.05% to about 0.25%, about 0.05% to about 0.20%, about 0.08% to about 0.30%, about 0.08% to about 0.25%, about 0.08% to about 0.20%, about 0.1% to about 0.30%, about 0.1% to about 0.25%, or about 0.1% to about 0.20%). For example, the alloy may contain 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 2%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0 It may contain 0.39%, 0.40%, all by weight.

[0073] In some examples, the aluminum alloys described herein may include copper (Cu) in the alloy. Up to about 0.4% (e.g., 0.0% to about 0.4%, 0.0% to about 0. 35%, about 0.02% to about 0.30%, about 0.05% to about 0.28%, about 0.06% to about 0.25%, approx. 0.8% to approx. 0.22%, approx. 0.1% to approx. 0.20%, approx. 0.1% to approx. 0 For example, about 0.18%, about 0.1% to about 0.16%, or about 0.1% to about 0.15%). The alloy contains Cu at 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12% ,0.13%,0.14%,0.15%,0.16%,0.17%,0.18%,0.1 9%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0. 26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0 .33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39% 0.4% or less. In some cases, Cu is absent from the alloy (i.e., 0. %). All percentages are by weight.

[0074] In some examples, the aluminum alloys described herein may further comprise magnesium (Mg): Up to about 0.5% (e.g., 0.0% to about 0.5%, about 0. 01% to 0.48%, 0.02% to 0.46%, 0.05% to 0.45%, 0.08% to 0.42%, 0.1% to 0.40%, 0.15% to 0.38%, About 0.18% to about 0.36%, about 0.2% to about 0.35%, or about 0.25% to about 0. For example, the alloy contains Mg at 0.10%, 0.11%, 0.12%, 0. 13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26% , 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33 %, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0. 4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0 In some cases, Mg may contain 0.47%, 0.48%, 0.49%, or 0.5%. Not included in the alloy (i.e., 0%). All percentages are expressed by weight.

[0075] In some examples, the aluminum alloys described herein may further comprise manganese (Mn) in the About 0.02% to about 0.1% (e.g., about 0.02% to about 0.0 9%, about 0.02% to about 0.08%, about 0.03% to about 0.7%, about 0.04% to about 0. 0.06%, about 0.05% to about 0.06%, about 0.05% to about 0.08%, or about 0.06 For example, the alloy contains 0.02%, 0.03%, 0.04% to about 0.09% Mn. %, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1% All percentages are expressed by weight.

[0076] In some examples, the aluminum alloys described herein may further include chromium (Cr) in the alloy. Up to about 0.25% (e.g., about 0.01% to about 0.25%, about 0 .01% to approx. 0.20%, approx. 0.01% to approx. 0.15%, approx. 0.02% to approx. 0.25%, Approximately 0.02% to approximately 0.20%, approximately 0.02% to approximately 0.15%, approximately 0.03% to approximately 0.25 %, about 0.03% to about 0.20%, or about 0.03% to about 0.15%). For example, The alloy contains 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0 .06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12% ,0.13%,0.14%,0.15%,0.16%,0.17%,0.18%,0.1 9%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, or 0.25 %. In some cases, Cr is absent (i.e., 0%) in the alloy. All by weight. Expressed as volume %.

[0077] In some examples, the aluminum alloys described herein may include one or both of titanium (Ti) and zinc (Zn). In some examples, the aluminum alloys described herein may include up to about 0.1% titanium (Ti) based on the total weight of the alloy (e.g., about 0.001% to about 0.08%, about 0.002% to about 0.005%, about 0.005% to about 0.06%, about 0.008% to about 0.06%, about 0.01% to about 0.05%, or about 0.02% to about 0.05%). For example, the alloy may contain 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1% Ti. In some cases, the alloy does not contain Ti (i.e., 0%). In some examples, the aluminum alloys described herein contain up to about 0.1% Zn (e.g., about 0.001% to about 0.08% or about 0.005% to about 0.06%) based on the total weight of the alloy. For example, the alloy may contain 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1% Zn. In some cases, Zn is absent (i.e., 0%) in the alloy. In some cases, Ti and Zn are absent (i.e., 0%) in the alloy. All expressed in weight percent.

[0078] Optionally, the aluminum alloys described herein may further include other trace elements, sometimes referred to as impurities, at 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. These impurities may include, but are not limited to, V, Ni, Sc, Hf, Zr, Sn, Ga, Ca, Bi, Na, Pb, or combinations thereof. Thus, V, Ni, Sc, Hf, Zr, Sn, Ga, Ca, Bi, Na, or Pb may be present in the alloy at 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. The sum of all impurities does not exceed 0.15% (e.g., 0.1%). All expressed in weight percent. The remaining percentage of each alloy may be aluminum.

[0079] The aluminum alloys described herein may include at least about 40% by weight of recycled content. For example, the aluminum alloys may include at least about 45% by weight, at least about 50% by weight, at least about 60% by weight, at least about 70% by weight, at least about 80% by weight, at least about 90% by weight, or at least about 95% by weight of recycled content.

[0080] In some examples, the aluminum alloy product has a yield strength of about 100 MPa or more, for example, in the T4 temper. For example, the aluminum alloy product may have a yield strength of 100 MPa or more, 105 MPa or more, 110 MPa or more, 115 MPa or more, 120 MPa or more, 125 MPa or more, 130 MPa or more, 135 MPa or more, or 140 MPa or more. In some cases, the yield strength is about 100 MPa to about 140 MPa (e.g., about 105 MPa to about 135 MPa, about 110 MPa to about 130 MPa, or about 115 MPa to about 125 MPa). The aluminum alloy products described herein may exhibit yield strengths as described herein when measured longitudinally (L), transversely (T), and / or diagonally (D), respectively, relative to the rolling direction.

[0081] In some examples, the aluminum alloy product has an ultimate tensile strength of about 200 MPa or more, for example, in the T4 temper. For example, the aluminum alloy product may have an ultimate tensile strength of 205 MPa or more, 210 MPa or more, 215 MPa or more, 220 MPa or more, 225 MPa or more, 230 MPa or more, 235 MPa or more, 240 MPa or more, 245 MPa or more, or 250 MPa or more. In some cases, the ultimate tensile strength is about 200MPa to about 250MPa (for example, about 205MPa to about 245MPa, about 210MPa The pressure ranges from about 215 MPa to about 235 MPa. The aluminum alloy products shown in the figure are rolled in the longitudinal (L) and transverse (T) directions. Ultimate tensile strength as described herein when measured in the longitudinal and / or diagonal (D) directions. It can show strength.

[0082] In some cases, the aluminum alloy product may have a uniformly low elongation, for example in the case of the T4 temper. For example, the aluminum alloy product may have at least about 20% and at most about 30%. Elongation 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29 %, or 30%, or anywhere in between. The aluminum alloy products are oriented in the longitudinal (L), transverse (T) and / or transverse (T) directions relative to the rolling direction. may exhibit uniform elongation as described herein when measured in the diagonal (D) direction.

[0083] In some cases, the aluminum alloy product may have low total elongation, for example in the case of T4 temper. For example, the aluminum alloy product may have a total elongation of about 27% and a maximum of about 35%. Approximately 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, or 35% The aluminum alloy products described herein may have any of the following properties: In the longitudinal (L), transverse (T) and / or diagonal (D) directions, respectively, When measured, it may exhibit a total elongation as described herein.

[0084] How to use The alloys and methods described herein are suitable for use in automotive applications, including motor vehicle, aircraft, and rail applications. and / or transportation applications, or any other desired application. The alloy and method are used to manufacture motor vehicle body parts, such as safety cages, whiteboards, etc. D, crash rail, bumper, side beam, roof beam, cross beam, pillar - Reinforcements (e.g. A-pillar, B-pillar, and C-pillar), inner panels, outer panels panels, side panels, inner hood, outer hood, or trunk lid panels. The aluminum alloys and methods described herein can also be used in aircraft or is used in rail vehicle applications and can also make exterior and interior panels, for example .

[0085] The alloys and methods described herein may also be used in electronics applications, such as external and internal For example, the alloys and methods described herein can be used to create portable electronic devices. It is also possible to create enclosures for electronic devices, including tablets and tablets. In some examples, the alloys are used to fabricate the outer casing of a mobile phone (e.g., a smartphone). The present invention can be used to create a housing for a tablet bottom chassis and a casing for a tablet bottom chassis. can be used for any other desired application, e.g. bottles, food containers, etc.

[0086] Examples of suitable methods and alloy products Example 1 is a method for producing an aluminum alloy product, which includes casting an aluminum alloy and casting Producing an aluminum alloy product, homogenizing the cast aluminum alloy product, and producing a cast aluminum alloy product; hot rolling the homogenized cast aluminum product; a hot rolled product having a thickness reduction of about 25% to 70%; cold rolling in a single cold rolling stage to produce a first cold rolled product having an intermediate gauge. The first cold rolled product is then subjected to a second cold roll process in which the thickness is reduced by about 40% to about 70% from the intermediate gauge. The cold rolling step involves cold rolling to produce the final gauge aluminum alloy product.

[0087] Example 2 further includes intermediate annealing the first cold rolled product. is a method as described in any of the subsequent examples.

[0088] Example 3 is a method as described in any of the preceding or subsequent examples, wherein the intermediate annealing step is conducted at an intermediate annealing temperature of about 300°C to about 450°C.

[0089] Example 4 is the method of any of the preceding or subsequent examples, wherein the intermediate gauge comprises a thickness of about 2 mm to about 6 mm.

[0090] Example 5 is the method of any of the preceding or subsequent examples, further comprising solution treating the final gauge aluminum alloy product to produce an aluminum alloy product.

[0091] Example 6 is the method of any of the preceding or subsequent examples, wherein the final gauge comprises a thickness of about 0.1 mm to about 3 mm.

[0092] Example 7 is the method of any of the preceding or subsequent examples, wherein the second cold rolling step results in a thickness reduction of about 40% to less than about 70% from the intermediate gauge.

[0093] Example 8 is a method as described in any of the preceding or following examples, wherein the casting step includes direct chill casting or continuous casting.

[0094] Example 9 is the method of any of the preceding or subsequent examples, wherein the homogenization step is carried out at a homogenization temperature of about 450°C to about 600°C.

[0095] Example 10 is the method of any of the preceding or subsequent examples, wherein the hot rolling step is conducted at a hot rolling temperature of from about 500°C to about 560°C.

[0096] Example 11 is the method of any of the preceding or subsequent examples, wherein the volume fraction of alpha fibers in the aluminum alloy product comprises at least about 8%.

[0097] Example 12 is the method of any of the preceding or subsequent examples, wherein the volume fraction of beta fibers in the aluminum alloy product comprises at least about 6%.

[0098] Example 13 is the method of any preceding or subsequent example, wherein the ratio of the volume fraction of alpha fibers to the volume fraction of beta fibers in the aluminum alloy product is from about 0.5:1 to 2:1.

[0099] Example 14 is a method as described in any of the preceding or subsequent examples, wherein the final gauge aluminum alloy product is isotropic.

[0100] Example 15 is the method of any of the preceding or subsequent examples, wherein the final gauge aluminum alloy product comprises a yield strength that is at least about 5% greater than the yield strength of an aluminum alloy produced by a process that includes a final cold rolling step in which the reduction in thickness from the intermediate gauge aluminum alloy to the final gauge aluminum alloy exceeds 70%.

[0101] Example 16 is the method of any of the preceding or subsequent examples, wherein the final gauge aluminum alloy product comprises an ultimate tensile strength that is at least about 3% greater than an ultimate tensile strength of an aluminum alloy produced by a process that includes a final cold rolling step in which the reduction in thickness from the intermediate gauge aluminum alloy to the final gauge aluminum alloy exceeds 70%.

[0102] Example 17 is a final cold rolling step in which the final gauge aluminum alloy product has a thickness reduction of more than 70% from the intermediate gauge aluminum alloy to the final gauge aluminum alloy. At least about 5% greater than the total elongation of an aluminum alloy produced by a process comprising: The method of any of the preceding or following examples has a total elongation.

[0103] Example 18 shows that the aluminum alloy contains about 0.5 to 2.0 wt. % Si, 0.1 to 0.4 % Fe, max. 0.4% Cu, max. 0.5% Mg, 0.02-0.1% % Mn, max 0.02% Cr, max 0.15% Ti, max 0.1% of Zn, up to 0.15 wt. % impurities, and Al, either in the preceding or succeeding examples. This is a method according to the present invention.

[0104] Example 19 shows that the aluminum alloy contains about 0.7 to 1.4 wt. % Si, 0.1 to 0.3 % Fe, max. 0.2% Cu, max. 0.4% Mg, 0.02-0.08% % Mn, max 0.015% Cr, max 0.05% Ti, max 0.1% % Zn, up to 0.15% by weight impurities, and Al. The method is either of the above.

[0105] Example 20 shows that the aluminum alloy contains about 1.0 to 1.4 wt. % Si, 0.12 to 0. 20% by weight Fe, max. 0.15% by weight Cu, max. 0.35% by weight Mg, 0.04~ 0.08% by weight Mn, 0.01-0.02% by weight Cr, max. 0.02% by weight Ti, 0.04% by weight max. Zn, 0.15% by weight max. impurities, and Al, A method as described in any of the subsequent examples.

[0106] Example 21 is a final gauge aluminum alloy product that constitutes an automobile body part. A method as described in any of the preceding or following examples.

[0107] Example 22 contains approximately 0.5-2.0 wt.% Si, 0.1-0.4 wt.% Fe, and a maximum of 0. 4 wt% Cu, max 0.5 wt% Mg, 0.02-0.1 wt% Mn, max 0.0 2% by weight Cr, max. 0.15% by weight Ti, max. 0.1% by weight Zn, max. 0.15% by weight % impurities and Al, and the microstructure of the aluminum alloy contains at least about 6% volume fraction of beta fibers.

[0108] Example 23 illustrates a method for producing an aluminum alloy having an alpha fiber volume fraction in the microstructure of at least The aluminum alloy of any of the preceding or following examples comprises about 8% or more of the aluminum alloy.

[0109] Example 24 shows the volume fraction of alpha fibers and the volume fraction of beta fibers in the aluminum alloy. The aluminum alloy of any preceding or subsequent embodiment, wherein the ratio of It is an aluminum alloy.

[0110] Example 25 is an aluminum alloy as described in any of the preceding or subsequent examples, which is isotropic. It is.

[0111] Example 26 is a leading or trailing edge having a final gauge thickness of about 0.1 mm to about 3 mm. The aluminum alloy according to any of the examples.

[0112] The following examples serve to further illustrate the invention but are not intended to limit it. Rather, it is to be understood that, after reading the description herein, one of ordinary skill in the art would be able to make such modifications without departing from the spirit and scope of the present invention. It is to be clearly understood that various embodiments, modifications, and equivalents thereof may be employed. can be. EXAMPLES

[0113] Example 1: Properties of aluminum alloy products Three aluminum alloy product samples (Alloys 1 to 3) having the compositions shown in Table 4 were prepared. Table 4 JPEG2025032283000005.jpg23150

[0114] In Table 4, all values ​​are in weight percent (wt. %) based on the total weight of the aluminum alloy composition. These alloys may contain aluminum and up to 0.15 wt. % total impurities.

[0115] Alloys 1-3 were each processed in three different ways, with the final downstream processing steps being varied to achieve various final cold reductions. As described in more detail below, alloys 1 and 2 were processed with a high final cold reduction and alloy 3 was processed with a low final cold reduction. Additionally, alloys 1 and 2 were each processed with a method that did not include an inter-batch annealing step.

[0116] FIG. 1A is a schematic diagram showing a processing method 100 for Alloy 1. Alloy 1 was direct chill cast to obtain an ingot 110. The ingot 110 was subjected to the homogenization step described above. The ingot 110 was then subjected to hot rolling in a reversing mill to rough roll the ingot 110, resulting in a 94% thickness reduction from 670 mm to 40 mm. After rough rolling, the ingot 110 was further subjected to hot rolling in a tandem mill to obtain a hot rolled product. During the hot rolling step in the tandem mill, the thickness of the ingot was reduced by 85%, from 40 mm to 6 mm. The hot rolled product was further subjected to cold rolling in a cold mill to obtain a final gauge aluminum alloy product. During the cold rolling step, the thickness of the hot rolled product was reduced by 85%, from 6 mm to 0.9 mm. In the manufacturing method of Alloy 1, the aluminum alloy article was subjected to a high final cold reduction and processed without an intermediate batch anneal.

[0117] 1B is a schematic diagram showing a second processing method 150 for Alloy 2. Alloy 2 was direct chill cast to obtain an ingot 110. The ingot 110 was subjected to the homogenization step described above. The ingot 110 was then subjected to hot rolling in a reversing mill to rough roll the ingot 110, resulting in a 94% thickness reduction from 670 mm to 40 mm. After rough rolling, the ingot 110 was further subjected to hot rolling in a tandem mill to obtain a hot rolled product. During this hot rolling stage in the tandem mill, the thickness of the ingot was reduced by 85%, from 40 mm to 6 mm. After hot rolling, the hot rolled product was coiled and cooled to room temperature. The cooled hot rolled product was further subjected to cold rolling in a cold mill to obtain a final gauge aluminum alloy product. During this cold rolling stage, the thickness of the hot rolled product was reduced by 85%, from 6 mm to 0.9 mm. In the method of manufacturing alloy 2, the aluminum alloy product was subjected to a high final cold reduction and processed without an intermediate batch anneal.

[0118] 2 is a schematic diagram illustrating a second processing method 200 according to the methods described herein. Alloy 3 was direct chill cast to obtain an ingot 210. The ingot 210 was subjected to the homogenization step described above. The ingot 210 was then subjected to hot rolling in a reversing mill to rough roll the ingot 210, resulting in a 94% thickness reduction from 670 mm to 40 mm. After rough rolling, the ingot 210 was subjected to further hot rolling in a tandem rolling mill to obtain a hot rolled product. During the hot rolling stage in the tandem rolling mill, the thickness of the ingot was reduced by 85%, from 40 mm to a thickness of 6 mm. The hot rolled product was subjected to further cold rolling (i.e., a first cold rolling stage) to produce a first cold rolled product.

[0119] In this first cold rolling stage, the thickness of the hot rolled product is reduced from 6 mm to 3 mm. This first cold rolled product was coiled and then placed in the batch intermediate annealing stage. In this intermediate batch annealing stage, the first cold rolled product Heat to a temperature of about 410°C at a heating rate of about 50°C / hour, soak for about 2 hours, and then cool. The coil was cooled to room temperature at a rate of about 12°C / hr. After the batch interanneal, the first cold The rolled product is then subjected to a second cold rolling step in a cold rolling mill to produce a final gauge aluminum alloy. In this second cold rolling step, the thickness of the first cold product was reduced from 3 mm to The thickness was reduced by 70% from 0.01 to 0.9 mm. This second cold rolling step resulted in a low final cold The reduction in thickness, for example, a reduction of 70% or less of the gauge thickness, occurred. The aluminum alloy product is cold rolled in two stages with an intermediate annealing stage between the first and second cold rolling stages. It was subjected to cold reduction processing.

[0120] FIG. 3 is a graph showing the distribution of texture components in the microstructures of alloys 1 to 3. The composite fiber component is made up of alpha fibers, e.g., cubic, goss, and rotational goss, and beta fibers. In FIG. 3, the first histogram bar for each set includes Represents alloy 1 processed under high (e.g., >70%) final cold reduction without batch annealing. The second histogram bar for each set does not include batch annealing and is The third histogram bar per set represents alloy 2 processed under final cold reduction (>100%). This represents alloy 3 that has been worked under low (e.g., 70% or less) final cold reduction, including annealing. Alloy 3 contains a higher amount of alpha fibers (e.g., 9%) than alloy 1 (e.g., 7%) and alloy 2 (e.g., 2.5%). Alloy 3 also showed a higher amount of beta fibers (e.g., 6%) compared to gold 2 (e.g., 6%). , 8%) compared to Alloy 1 (e.g., 5%) and Alloy 2 (e.g., 5%). Alloy 3, which was annealed and worked under low final cold rolling, showed a high final cold rolling pressure. The samples showed a larger amount of texture compared to the samples processed without annealing. In particular, alloy 3 has a high ratio of alpha and beta fibers, which is favorable for uniform elongation. Alloy 3 had a balanced distribution of non-linear texture components. The alpha and beta fiber contents were similar.

[0121] FIG. 4 is a graph showing the yield strength of test samples taken from Alloy 1, Alloy 2, and Alloy 3. The tensile properties are all measured in the longitudinal (called "L") and transverse (called "R") directions relative to the rolling direction of the process. The evaluation was done in three directions, including horizontal (called "T") and diagonal (called "D"). Alloy 1 and Alloy 2 were processed according to the methods shown in Figs. 1A and 1B, respectively, and were batch-rolled during cold rolling. The alloys did not include an intermediate annealing step and were processed under a high (e.g., greater than 70%) final cold reduction. Alloy 3 was cold rolled according to the method of FIG. 2, including an intermediate batch annealing step during cold rolling; and The first histogram bar in each set is The first histogram bar per set represents alloy 1, the second histogram bar per set represents alloy 2, and the third histogram bar per set represents alloy 3. The gram bars represent Alloy 3. As shown in Figure 4, the yield strength of both Alloy 1 and Alloy 2 in the T4 temper is The strength was lower than the yield strength of Alloy 3 regardless of the direction of the tensile test. In the direction, the yield strength of both alloy 1 and alloy 2 is 99MPa to 113MPa, and that of alloy 3 is 113MPa. The yield strength of the steel was 114MPa to 122MPa, and it showed isotropic tensile properties. Additionally, Alloy 3 exhibits excellent yield strength, which in turn makes it suitable for a variety of automotive applications, e.g., structural parts. Molding with sufficient strength for the purpose of The results showed that the aluminum alloy has high corrosion resistance.

[0122] Figure 5 shows the ultimate tensile strength of test samples taken from Alloy 1, Alloy 2, and Alloy 3. 5 is a graph showing the results of the fabrication, processing, and testing of the embodiment of FIG. Tensile properties are shown in pairs based on the test direction (i.e., L, T, or D) above. For each pair, the first histogram bar represents alloy 1 and the second histogram bar represents alloy 2. The third histogram bar per set represents alloy 3. As shown in Figure 5, alloy 3 Alloy 3 exhibited superior ultimate tensile strength, thus indicating a highly formable aluminum alloy with sufficient strength for various automotive applications. In fact, Alloy 3, which was batch annealed and processed under a low final cold reduction, had a higher ultimate tensile strength than Alloy 1 and Alloy 2, which did not include batch annealing and were processed under a high final cold reduction.

[0123] FIG. 6 is a graph showing the uniform elongation of test samples taken from Alloy 1, Alloy 2, and Alloy 3. Formability properties were evaluated in three directions including longitudinal (referred to as "L"), transverse (referred to as "T"), and diagonal (referred to as "D"), all relative to the rolling direction of processing. Alloy 1 and Alloy 2 were processed according to the methods shown in FIGS. 1A and 1B above, respectively, and Alloy 3 was processed according to the method shown in FIG. 2 above, under batch annealing and low final cold reduction. FIG. 6 shows the uniform elongation properties in sets based on the above directions (i.e., L, T, or D). The first histogram bar per set represents Alloy 1, the second histogram bar per set represents Alloy 2, and the third histogram bar per set represents Alloy 3. As shown in Figure 6, Alloy 3 exhibited equal or greater uniform elongation in each direction (L, T, and D) compared to Alloy 1 and Alloy 2.

[0124] FIG. 7 is a graph showing the total elongation of test samples taken from alloy 1, alloy 2, and alloy 3. Alloy 1 and alloy 2 were processed according to the methods described above and shown in FIGS. 1A and 1B, respectively, while alloy 3 was processed according to the method described above in FIG. 2, under batch annealing and low final cold reduction. In FIG. 7, the elongation properties are shown in sets based on the direction described above (i.e., L, T, or D). The first histogram bar per set represents alloy 1, the second histogram bar per set represents alloy 2, and the third histogram bar per set represents alloy 3. As shown in FIG. 7, the total elongation of alloy 3 in the T4 temper was 29-32% regardless of the method of tensile testing, indicating the isotropic nature of alloy 3. Alloy 2 has similar total elongation in the L and D directions, while alloy 3 achieved a greater total elongation in the T direction. Additionally, Alloy 3 exhibited the same or higher total elongation in each of the L, T, and D directions compared to Alloy 2 while requiring less cold work and using less energy in each cold work step. Additionally, Alloy 3 exhibited more uniform elongation in each of the L, T, and D directions compared to Alloys 1 and 2.

[0125] FIG. 8 is a graph showing n values ​​(i.e., increase in strength after deformation) for Alloy 1, Alloy 2, and Alloy 3, each prepared and processed as described above. In FIG. 8, the n values ​​are shown in sets based on their orientation (i.e., L, T, or D). The first histogram bar per set represents Alloy 1, the second histogram bar per set represents Alloy 2, and the third histogram bar per set represents Alloy 3. As shown in FIG. 8, Alloy 3 exhibited equal or greater n values ​​and thus improved formability compared to Alloys 1 and 2.

[0126] FIG. 9 is a graph showing the bulge test values ​​for Alloy 2 and Alloy 3, each prepared and processed as described above. The bulge test measures the ability of an alloy to deform after large strain under biaxial stress. The test is performed by deforming a rigidly clamped square blank with pressurized hydraulic fluid. The pressurized fluid creates a frictionless force that deforms the material. One parameter used to measure the performance of an alloy during a bulge test is the maximum distance the material will deform before failure, e.g., bulge height. As shown in FIG. 9, Alloy 3 had a higher bulge height than Alloy 2. For example, Alloy 3 had a bulge height 6% higher than Alloy 2.

[0127] FIG. 10 is a graph showing the r-values ​​for Alloy 1, Alloy 2, and Alloy 3, each prepared and processed as described above. Alloy 1 and Alloy 2 were processed according to the method described above and shown in FIGS. 1A and 1B, respectively, and Alloy 3 was processed according to the method shown in FIG. 2 above, under batch annealing and low final cold reduction. In FIG. 10, the r-values ​​are presented in sets based on the direction (i.e., L, T, or D) described above. As described above, the r-value measures the ability to deform after large strains under biaxial stress conditions. This test is performed by deforming a rigidly clamped square blank with pressurized hydraulic fluid. The pressurized fluid creates a frictionless force that deforms the material. As shown in Figure 10, Alloy 3 has the smallest variation in r-value between the stress directions, and its isotropic For example, alloy 3 showed a deviation of about 38% in the r-value between the L and D directions. Alloy 1 showed a deviation of about 40% in r-value between the L and D directions. Alloy 3 showed a deviation of about 40% between the T and D directions. The r-value of alloy 1 showed a deviation of about 29% between the T and D directions, while the r-value of alloy 2 showed a deviation of about 29% between the T and D directions. Alloy 3 showed a deviation of about 12.7% in the r-value between the L and T directions. However, alloy 2 showed a deviation of about 12.8% in the r-value between the L and T directions.

[0128] Alloy 2 and Alloy 3 were each subjected to a cross die test. Using a die tool, the clamping force was 15kN, the stamping speed was 8mm / sec, and the stamping The starting blank size was 250 mm wide and 250 mm long. The starting thickness was 0.9 mm. These samples were sprayed using an electrostatic spray tube. 0.5g / m2 hot melt 2 The potential wear during cross-die testing was measured using The friction effect was eliminated. Alloy 3 performed better than Alloy 2 in the cross die stamping test. Specifically, alloy 3 gave a deep drawing of 65 mm, and alloy 2 gave a deep drawing of 55 mm. He gave it a go.

[0129] All patents, publications, and abstracts cited above are hereby incorporated by reference in their entirety. Various embodiments of the present invention are described to accomplish various objectives of the present invention. It should be recognized that these embodiments are merely illustrative of the principles of the present invention. Many of these modifications and adaptations fall within the spirit and scope of the present invention as defined in the following claims. It will be readily apparent to one skilled in the art without departing from the principles of the present invention.

Claims

1. Casting the aluminum alloy to produce a cast aluminum alloy product; homogenizing said cast aluminum alloy product to produce a homogenized cast aluminum alloy product; hot rolling the homogenized cast aluminum product to produce a hot rolled product; cold rolling the hot rolled product in a first cold rolling step having a thickness reduction of about 25% to 70% to produce a first cold rolled product having an intermediate gauge; and cold rolling said first cold rolled product in a second cold rolling step where the thickness is reduced by about 40% to about 70% from said intermediate gauge to produce a final gauge aluminum alloy product.

2. The method of claim 1 further comprising intermediate annealing said first cold rolled product.

3. The method of claim 2, wherein the intermediate annealing step is carried out at an intermediate annealing temperature of about 300°C to about 450°C.

4. The method of any one of claims 1 to 3, wherein the intermediate gauge comprises a thickness of about 2 mm to about 6 mm.

5. The method of any one of claims 1 to 4, further comprising solution treating said final gauge aluminium alloy product.

6. The method of any one of claims 1 to 5, wherein the final gauge comprises a thickness of about 0.1 mm to about 3 mm.

7. The method of any one of claims 1 to 6, wherein the second cold rolling step reduces the thickness by about 40% to less than about 70% from the intermediate gauge.

8. The method of any one of claims 1 to 7, wherein the casting step comprises direct chill casting or continuous casting.

9. The method of any one of claims 1 to 8, wherein the homogenization step is carried out at a homogenization temperature of about 450°C to about 600°C.

10. The method of any one of claims 1 to 9, wherein the hot rolling step is carried out at a hot rolling temperature of about 500°C to about 560°C.

11. The method of any one of claims 1 to 10, wherein the volume fraction of alpha fibers in the aluminum alloy product comprises at least about 8%.

12. 12. The method of any one of claims 1 to 11, wherein the volume fraction of beta fibers in the aluminium alloy product comprises at least about 6%.

13. 13. The method of any one of claims 1 to 12, wherein the ratio of the volume fraction of alpha fibers to the volume fraction of beta fibers in the aluminum alloy product is about 0.5:1 to 2:

1.

14. said final gauge aluminum alloy product having a yield strength at least about 5% greater than that of an aluminum alloy produced by a process including a final cold rolling step in which the reduction in thickness from said intermediate gauge aluminum alloy to said final gauge aluminum alloy exceeds 70%. The method of any one of claims 1 to 13, wherein the yield strength is indicated.

15. The final gauge aluminum alloy product is A final cold rolling step in which the reduction in thickness to the final gauge aluminum alloy is greater than 70% is performed. The ultimate tensile strength of the aluminum alloy produced by the method comprising the steps of: % greater ultimate tensile strength.

16. The final gauge aluminum alloy product is A final cold rolling step in which the reduction in thickness to the final gauge aluminum alloy is greater than 70% is performed. A total elongation of at least about 5% greater than the total elongation of an aluminum alloy produced by a method including the steps of: The method according to any one of claims 1 to 15, wherein the elongation is achieved.

17. The aluminum alloy contains about 0.5 to 2.0 wt. % Si, 0.1 to 0.4 wt. % F. e. Maximum 0.4 wt.% Cu, Maximum 0.5 wt.% Mg, 0.02-0.1 wt.% Mn , max 0.02 wt.% Cr, max 0.15 wt.% Ti, max 0.1 wt.% Zn, max The method according to any one of claims 1 to 16, comprising at most 0.15% by weight of impurities and Al. Law.

18. Approximately 0.5-2.0 wt% Si, 0.1-0.4 wt% Fe, max. 0.4 wt% C u, max 0.5 wt% Mg, 0.02-0.1 wt% Mn, max 0.02 wt% C r, max. 0.15 wt.% Ti, max. 0.1 wt.% Zn, max. 0.15 wt.% impurities and an aluminum alloy comprising Al, the microstructure of the aluminum alloy comprises at least about 6% volume fraction of beta fibers; The aluminum alloy.

19. The volume fraction of alpha fibers in the microstructure of the aluminum alloy comprises at least about 8%.

20. The aluminum alloy of claim 18,

20. the ratio of the volume fraction of alpha fibers to the volume fraction of beta fibers in the aluminum alloy is about The aluminum according to any one of claims 18 and 19, wherein the ratio is from 0.5:1 to 2:

1. alloy.